Evidence that task performance should be distinguished from contextual performance. - Motowidlo, Stephan J.; Van Scotter, James R. (Journal of Applied Psychology, 1994)
This study tests the merit of the distinction made by W. C. Borman and S. J. Motowidlo (1993) between task performance and contextual performance. Supervisors rated 421 U.S. Air Force mechanics on their task performance, contextual performance, and overall performance. Data on length of air force experience, ability, training performance, and personality were also available for many of these mechanics. Results showed that both task performance and contextual performance contribute independently to overall performance. Experience is more highly correlated with task performance than with contextual performance, and personality variables are more highly correlated with contextual performance than with task performance. These results support the distinction between task performance and contextual performance and confirm that performance, at least as judged by supervisors, is multidimensional